Perceived Infertility and Contraceptive Use in the Female, Reproductive Age Cancer Survivor - Hadnott, Tracy N. (Fertil Steril, 2019)
OBJECTIVE: To estimate the association between perceived fertility potential and contraception use and to characterize factors important in contraceptive decision-making in reproductive-aged, female cancer survivors DESIGN: Cross-sectional study SETTING: Participants were from two state cancer registries, physician referrals, and cancer survivor advocacy groups in the United States PATIENTS: 483 female survivors aged 18–40 INTERVENTIONS: Online questionnaire MAIN OUTCOME MEASURES: Contraception use RESULTS: Eighty-four percent of participants used contraception; 49.7% utilized highly effective, World Health Organization Tier I and II methods (surgical sterilization, intrauterine devices, contraceptive implant, combined hormonal contraceptives, medroxyprogesterone acetate, progestin only pills, contraceptive diaphragm). Contraception non-use was more common among survivors who perceived themselves to be infertile, compared to survivors who perceived themselves to be as or more fertile than similarly aged peers (PR 4.0, 95% CI 2.5–7.4). In mediation analysis that adjusted for clinical infertility, 59% of the association between prior chemotherapy and contraception non-use was explained by perceived infertility. Contraception efficacy (n=62, 25.8%) and ease of use (n=50, 20.8%) were the most cited reasons for using Tier I/II methods; compared with lack of hormones (n=81, 49.7%) as the predominant reason for using less effective, Tier III/IV methods (P<0.001). CONCLUSION: While female, reproductive-age cancer survivors had high uptake of contraception, those who perceived themselves to be infertile were less likely to use contraception. Throughout survivorship, clinicians should counsel survivors on fertility potential in the context of their prior cancer treatments and on factors including contraceptive efficacy and hormone-free contraception that inform reproductive decision-making in this population.